Predictors of physical activity levels of individuals following traumatic brain injury remain unclear: A systematic review. (6th June 2016) - Hamilton, Megan; Khan, Michelle; Clark, Ross; Williams, Gavin; Bryant, Adam
Abstract: Objective : To identify factors which influence physical activity levels (PALs) of people with traumatic brain injury (TBI). Data sources : Eight electronic databases. Study selection : A systematic search was performed to identify articles that reported the measurement (quantity) of PALs of individuals with TBI. Data extraction/synthesis : Two authors reviewed andextracted the data independently. Article quality was evaluated using the Law critical review tool. Results : Six studies were identified that met the inclusion criteria. All studies found that PALs of participants with TBI were below those recommended for health benefits. Although a number of environmental and personal barriers restricted PA participation, motivation and exercise self-efficacy were the most frequently identified facilitators of PA in the TBI population. Despite apparent links, the relationship between mobility capacity and PALs was unclear from the results of this systematic review. Conclusion : The results of this systematic review demonstrated that little is known about PALs of individuals with TBI. PALs of participants with TBI were less than required for health maintenance. Self-efficacy to exercise and motivation were the most frequently identified facilitators of PA in the TBI population.